KIRGANELIA RETICULATA (POIR) BAILL.-A REVIEW ON ITS BOTANY, ETHNOBOTANY, PHYTOCHEMISTRY AND PHARMACOLOGY - Soni, Rajesh Kumar; Dixit, Vihangesh; Chandra, Akanksha; Irchhaiya, Raghuveer; Singh, Nandlal; Singh, Harsh (Journal of Drug Delivery and Therapeutics, 2013)
Ethnopharmacological relevance: Kirganelia reticulata (Poir.) Baill. is known for its importance in various traditional medicine around the world and are proved pharmacologically as an antiviral against Hepatitis B, hepatoprotective, antidiabetic and antioxidant. In Ayurvedic system of Indian medicine recognized its activity against jaundice, diuretic, fever, liver disorder, in bleeding gums, small pox, syphilis, etc. Aim of the review: The review summarizes the up-to-date and comprehensive information concerning the botany, traditional use, phytochemistry and pharmacology of important drug. Kirganelia reticulata and discusses the possible future scope for future research. Material and methods: In present review covers a literature survey across from 1932 to 2012. The some information collected from published literature on species of Kirganelia reticulata (Poir.) Baill. (=Syn. Phyllanthus reticulatus Poir.) and traditional ayurvedic texts. Results: Phytochemical studies have shown the presence of many valuable compounds such as lignans, flavonoids, steroids, coumerins, triterpenes, phenols, flavonones, alkaloids are common compounds in test species. The extract and the compounds isolated from Kirganelia reticulata show a wide spectrum of Biological activities including antidiabetic, antibacterial, antioxidant, hepatoprotective, antiplasmodial, anticiceptive, analgesic and anti-inflammatory properties. Conclusion: The present review summarizes information concerning the morphology, ecology, ethanopharmacologically, phytochemistry, and traditional diseases and applications of K. reticulata. This review target at gathering the research work undertaken till date on this plant in order to provide sufficient baseline information for future works and commercial exploitation.